PD-1 inhibitor inducing exosomal miR-34a-5p expression mediates the cross talk between cardiomyocyte and macrophage in immune checkpoint inhibitor–related cardiac dysfunction. Issue 2 (28th October 2020) - Xia, Wenzheng; Chen, Hanbin; Chen, Didi; Ye, Yijia; Xie, Congying; Hou, Meng
Abstract : Background: Immune checkpoint inhibitors (ICIs) have been an important therapeutic advancement in the field of cancer medicine. Recent reports provided greater insights into the cardiovascular adverse events, which prohibited the use of ICIs. Cardiovascular adverse events occur in different forms, such as myocarditis and cardiomyopathy, myocardial fibrosis, heart failure and pericardial disease. Cardiac aging overlapped with the occurrence of some cardiac diseases. Exosomes mediate cell–cell cross talk in cardiac diseases by transferring a variety of biomolecules, including microRNAs (miRs). miR-34a-5p is a well-known miR associated with the cardiac senescence. This study aimed to investigate whether cardiovascular adverse effects of the programmed cell death 1 (PD-1) inhibitor, a widely used ICI, were related to exosomal-transferred miR-34a-5p in cardiac senescence in a mouse model. Methods and results: The upregulation of miR-34a-5p in cardiomyocytes induced by exosomes derived from PD-1 inhibitor–treated macrophages, accompanied by cardiac senescence, caused cardiac injury in mouse hearts. miR-34a-5p was identified as an exosomal transfer RNA to induce cardiac senescence–related injury. Inhibiting miR-34a-5p in macrophages attenuated the exosome PD-1 inhibitor -induced pro-senescent effect in cardiomyocytes. TargetScan and luciferase assay showed that miR-34a-5p targeted the serine/threonine-protein phosphatase 1 regulatory subunit 10 (PNUTS) 3′-untranslated region. Conclusions: Exosomes derived from PD-1 inhibitor–treated macrophages exerted a pro-senescent effect by modulating the miR-34a-5p/PNUTS signaling pathway. The findings might supply new targets to ameliorate cardiac injury in patients with cancer receiving PD-1 inhibitor treatment.